Administração por convênios, um instrumento gerencial de políticas: uma análise dos convênios da Secretaria de Estado da Saúde de São Paulo - 1987 Administration by agreement a management tool of health policies: an analysis of agreements made by the Health Secretariat of S. Paulo State, Brazil - 1987 - Evelin Naked de Castro Sá; Maria Celina Guimarães Rabello (Universidade de São Paulo, 1988)
Foi realizada análise dos 1.141 convênios vigentes no primeiro semestre de 1987, celebrados pela Secretaria de Saúde do Estado de São Paulo, segundo os objetivos dos convênios e entidades conveniadas. Foram consideradas as potencialidades do convênio como instrumento de execução de políticas públicas de saúde e as necessidades de resposta organizacional da Secretaria para definição, acompanhamento, avaliação e controle dos convênios. Foram recomendadas algumas medidas para aumentar o rendimento de ações conveniadas para aperfeiçoar a expressão orçamentário-financeira da administração por convênios, com base num plano abrangente das ações de saúde. Research was carried out into 1,141 agreements made by the State Health Department of S. Paulo State, Brazil, and which were in force during the first semester of 1987. An analysis was made of the objectives of the agreements and the entities with which they were made and of the potentialities of the agreements as such as tools for the execution of public health policies as well as of the need for an organizational answer on the part of the State Health Department for the definition, follow-up and control of the agreements. Some patterns of action with a view to increasing the efficacy of the activities agreed on, for the improvement of the budgetary and financial expressions of the administration by means of agreements, on the overall basis of comprehensive planning of health actions, are recommended.